Fostering Vicarious Resilience for Perinatal Palliative Care Professionals - Grauerholz, Kathryn R.; Fredenburg, Michaelene; Jones, Premala Tara; Jenkins, Kristy N. (Frontiers in Pediatrics, 2020)
Background: The demands on health care professionals caring for families grappling with a life- limiting condition in an unborn or newly born child can be overwhelming. The provision of exemplary palliative care requires a cohesive interdisciplinary team of seasoned professionals resilient to daily challenges. In September 2019, the American College of Gynecology, in a committee opinion, published standard of care guidelines for perinatal palliative care. This has created an impetus for exceptional caregiving and a greater demand for both physician and interdisciplinary healthcare provider education, training, and ongoing support that promotes truly beneficent care for pregnant patients confronted with life-limiting fetal conditions. Methods: A scoping review of the research literature was conducted in order to distinguish the barriers and facilitators of professional resiliency in perinatal palliative care. PubMed, Medline, CINAHL, and EBSCO Psychology & Behavioral Sciences Collections were systematically reviewed. Because of the paucity of studies specific to perinatal palliative care, several interviews of nurses and physicians in that field were conducted and analyzed for content distinctly, pertaining to personal practices or work place factors that support or hinder professional resiliency. Results: The research indicated that medical professionals often cite a lack of knowledge, inexperience using effective communication skills related to perinatal palliative care and bereavement, challenges with interdisciplinary collaboration, misconceptions about the role and function of palliative care in the perinatal or neonatal settings, moral distress, and workload challenges as encumbrances to professional satisfaction. Strategic implementation of facility-wide bereavement care training, effective communication modalities, and evidenced-based practical applications are critical components for a thriving perinatal palliative care team. Authentic formal and informal debriefing, peer mentoring, adequate caseloads, robust provider self-care practices, exceptional relational efficacy, and cultural and spiritual humility can foster personal growth and even vicarious resilience for perinatal palliative care professionals. Conclusions: Support should be to be strategic and multi-faceted. The onus to implement salient measures to cultivate resilience in the perinatal palliative caregiver should not be only upon the individuals themselves, but also upon prevailing regulatory governing bodies and healthcare institutions as well.